Science Learning Innovation Using Augmented Reality Technology to Achieve Sustainable Development Goals (SDGs) through Increasing Students' Critical Thinking Abilities - Ramdani, Agus; Purwoko, Agus Abhi; Sukarso, AA; Sucilestari, Ramdhani (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to produce inquiry-based AR media that is feasible, practical, and effective to improve students' critical thinking skills which can ultimately achieve the SDGs goals in the aspect of mutual education. This study uses a 4D model development procedure. The subjects of this study were grade VIII students at one of the Mataram City Junior High Schools consisting of 3 classes. Data collection techniques used questionnaires, observation sheets and test instruments developed according to critical thinking indicators. Data analysis techniques used Aikens'V for feasibility testing, practicality percentage testing and normalized gain testing to test the hypothesis. Based on the results of the study, it was obtained that the Augmented Reality (AR) Media developed was included in the category of feasible and practical for use in science learning and could increase students' interest in learning. AR media supports students in the inquiry learning process. The use of AR media makes it easier for students to learn and provides fun and current things. Learning using AR media facilitates active and creative learning for pupils since it is supported by investigative activities.